Zanthoxylum bungeanum seed oil inhibits tumorigenesis of human melanoma A375 by regulating CDC25A/CyclinB1/CDK1 signaling pathways in vitro and in vivo - Wang, Wanting; Pang, Wenwen; Yan, Suying; Zheng, Xiaoli; Han, Qiurong; Yao, Yao; Jin, Leixin; Zhang, Chunze (Frontiers in Pharmacology, 2023)
Background: Zanthoxylum bungeanum seed oil (ZBSO) is extracted from the seeds of the traditional Chinese medicine Zanthoxylum bungeanum Maxim, which has been shown to have anti-melanoma effects. However, the specific mechanisms are not illustrated adequately. Aims: To further investigate the mechanism by which ZBSO inhibits melanoma and to provide scientific evidence to support ZBSO as a potential melanoma therapeutic candidate. Methods: CCK-8 assays were used to detect the function of ZBSO on A375 cells. Based on transcriptomics analyses, Western blot analysis was applied to determine whether an association existed in ZBSO with the CDC25A/CyclinB1/CDK1 signaling pathway. In addition, RT-qPCR and immunohistochemistry analysis validated that ZBSO has the anti-melanoma effect in a nude mouse xenograft model of human melanoma. Then, 16S rRNA sequencing was used to detect the regulation of gut microbes. Results: Cellular assays revealed that ZBSO could inhibit A375 cell viability by regulating the cell cycle pathway. Further studies presented that ZBSO could constrain CDC25A/CyclinB1/CDK1 signaling pathway in vitro and in vivo models of melanoma. ZBSO did not produce toxicity in mice, and significantly reduced tumor volume in xenotransplants of A375 cells. Genome analysis indicated that ZBSO successfully altered specific gut microbes. Conclusions: ZBSO inhibited the growth of A375 cells by regulating CDC25A/cyclinB1/CDK1 signaling pathway both in vitro and in vivo, suggesting that ZBSO may be a novel potential therapeutic agent.